Unleashing youth potentials in developing the agricultural sector - Man, Norsida (Universiti Putra Malaysia Press, 2012)
The participation of youth in agriculture is imperative given the fact that the hope and aspiration of agriculture, and the nation for that matter, rest on their shoulders. This successful and persistent youth in agriculture would pave their paths to be nucleus farmers. Youth involvement in trying out or getting involved in agriculture very much depends on their perception on agriculture itself. This research seeks to identify the perception of youth on agriculture and in particular it seeks to: 1) study the respondents’ profiles among the youth link to agriculture; 2) to study their perception on agriculture; and 3) to identify the agriculture education programme provided for the youth. The positive view on agriculture that is suggested by the research indicates that the youth do not totally deny or place a negative image on agriculture. Various agriculture education programmes have been and are currently organized to develop agriculture education among youth either by the government or the private agencies. In general, the young farmers are unaware of the programmes organized by the government or the private agencies. This shows ineffective communication for the beneficiary (youth) and the organizer of the programme. Effective agriculture education actually depends on how far and significant the commitment given by every party. Multiple efforts are needed to ensure the effectiveness of an education programme.